2014
DOI: 10.22323/2.13030201
|View full text |Cite
|
Sign up to set email alerts
|

War, anxiety, optimism and triumph: a study on science in the main Brazilian TV news

Abstract: We analysed the representations of science and of scientists at Jornal Nacional, the main Brazilian TV news. We carried out content and frames analysis, besides the lexical and semantic analysis of the transcriptions of the science and technology stories. Our results show a narrative that highlights the novelties and the epopee of the scientific advance, mainly in the health field. But to the emotional palette feelings of combat, anxiety and triumph were added. The face of the scientist presented by the TV new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Confidence in the success of the announced research, emphasis on hard news and the little attention paid to controversy, scientific uncertainties, and difficulties to be faced in the course of the work dominated the 214 journalistic stories on biologically active compounds published over the course of 27 years, which was fairly similar to the coverage of science news on TV [Castelfranchi, Massarani and Ramalho, 2014;Ramalho et al, 2016]. The optimism about the future of compounds in the initial phase of evaluation was inconsistent and reflects the lack of knowledge about drug development and the peculiarities of scientific production and represents an attempt to draw the attention of readers, as argued by Dentzer [2009], creating expectations that can hardly be met.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Confidence in the success of the announced research, emphasis on hard news and the little attention paid to controversy, scientific uncertainties, and difficulties to be faced in the course of the work dominated the 214 journalistic stories on biologically active compounds published over the course of 27 years, which was fairly similar to the coverage of science news on TV [Castelfranchi, Massarani and Ramalho, 2014;Ramalho et al, 2016]. The optimism about the future of compounds in the initial phase of evaluation was inconsistent and reflects the lack of knowledge about drug development and the peculiarities of scientific production and represents an attempt to draw the attention of readers, as argued by Dentzer [2009], creating expectations that can hardly be met.…”
Section: Resultsmentioning
confidence: 95%
“…The author concluded that the news uncritically adhered to the presuppositions of pharmaceutical companies, emphasised the novelties and benefits of the new drugs, rarely mentioned their side effects, avoided controversy and presented the results of scientific research as unquestionable truths. This approach is not limited to the coverage about new drugs: the emphasis on novelties, optimism and a triumphalist tone characterised the science stories transmitted from April 2009 to March 2010 in Jornal Nacional, the main Brazilian newscast [Castelfranchi, Massarani and Ramalho, 2014]. Comparative studies recorded the value of scientific production and of national scientists also in Argentina, Mexico and Colombia [Massarani et al, 2008;Ramalho et al, 2016].…”
mentioning
confidence: 99%
“…The body of scholarly research in our sample clearly shows that the media in developing countries often fail to present S&T events and issues with an adequate evaluation of the scientific rigour behind them – such as methodological strengths/weaknesses, weight of evidence, scientific consensus, ethical conduct and so on (e.g. Castelfranchi et al, 2014; DeRosier et al, 2015; Du and Rachul, 2012; Jurberg et al, 2009; Lü, 2009; Masood, 2005; Midttun et al, 2015; Navarro et al, 2011; Ogbogu et al, 2013; Panopio and Navarro, 2011; Ramalho et al, 2012). Shanahan’s (2009) review of climate coverage in 12 countries, for example, finds that, except for India, such coverage rarely employs scientific facts to support or substantiate stories, or to analyse causes and effects.…”
Section: The Scarcity Of Critical Science Reportingmentioning
confidence: 99%
“…Crawley [2007] used computer aid in a qualitative analysis about the coverage of biotechnologies in agriculture in community daily news. Thanks to the use of specifically built dictionaries and others available on the emotional and cognitive dimensions of language, Castelfranchi, Massarani and Ramalho [2014], identified that the discourse of scientific dissemination in important Brazilian TV programs was marked by metaphors of war, aggression, and heavily marked by gender inequalities.…”
Section: Computer-aided Analyses In Public Communication Of Science Amentioning
confidence: 99%